Impaired Neurofilament Integrity and Neuronal Morphology in Different Models of Focal Cerebral Ischemia and Human Stroke Tissue - Mages, Bianca; Aleithe, Susanne; Altmann, Stephan; Blietz, Alexandra; Nitzsche, Björn; Barthel, Henryk; Horn, Anja K. E.; Hobusch, Constance; Härtig, Wolfgang; Krueger, Martin; Michalski, Dominik (Frontiers in Cellular Neuroscience, 2018)
As part of the neuronal cytoskeleton, neurofilaments are involved in maintaining cellular integrity. In the setting of ischemic stroke, the affection of the neurofilament network is considered to mediate the transition towards long-lasting tissue damage. Although peripheral levels of distinct neurofilament subunits are shown to correlate with the clinically observed severity of cerebral ischemia, neurofilaments have so far not been considered for neuroprotective approaches. Therefore, the present study systematically addresses ischemia-induced alterations of the neurofilament light (NF L), medium (NF M) and heavy (NF H) subunits as well as of α internexin (INA). For this purpose, we applied a multi-parametric approach including immunofluorescence labeling, Western Blotting, qRT PCR and electron microscopy. Analyses comprised ischemia-affected tissue from three stroke models of middle cerebral artery occlusion (MCAO), including approaches of filament-based MCAO in mice, thromboembolic MCAO in rats and electrosurgical MCAO in sheep, as well as human autoptic stroke tissue. As indicated by altered immunosignals, impairment of neurofilament subunits was consistently observed throughout the applied stroke models and in human tissue. Thereby, altered NF L immunoreactivity was also found to reach penumbral areas, while protein analysis revealed consistent reductions for NF L and INA in the ischemia-affected neocortex in mice. At the mRNA level, the ischemic neocortex and striatum exhibited reduced expressions of NF L- and NF H-associated genes, whereas an upregulation for Ina appeared in the striatum. Further, multiple fluorescence labeling of neurofilament proteins revealed spheroid and bead-like structural alterations in human and rodent tissue, correlating with a cellular edema and lost cytoskeletal order at the ultrastructural level. Thus, the consistent ischemia-induced affection of neurofilament subunits in animals and human tissue, as well as the involvement of potentially salvageable tissue qualify neurofilaments as promising targets for neuroprotective strategies. During ischemia formation, such approaches may focus on the maintenance of neurofilament integrity, and appear applicable as co-treatment to modern recanalizing strategies.